Membangun Mekanisme Fembuatan Kebijakan Negara yang Partisipatif - Author: Muntoha (Jurnal Hukum IUS QUIA IUSTUM, 2003)
Itis common that in Indonesia, the economic considerations, stability and securityoften overcome considerations on society aspiration and their right as citizen. Otherwise people would respond warmly the changes made if they are invited to take a part in planning to create the changes. Theprocess must be taken when it starts to design, reconstruct, implement and evaluate them.